Sexual Health Education (SaHEM) - Hasan, Haliza; Abdul Hamid, Siti Hazariah; Mohamad Ismail, Mohamad Firdaus; A. Razak, Nor'nasuha; Ramlee, Muhammad Amiezul Ashraf; Alius, Muhammad Rafe; Musahuddin, Muhammad Nadzmi Syazwan; Noordin, Naqib Syahir; Ibrahim, Mohamad Zaidi (2021)
SeHEM was designed as a module for teaching and learning, that can be used at the Community-Based Rehabilitation Centre in Kuantan and will be expanding the implementation to the whole Pahang. This disclosure consisted of 3 parts on sexual health education according to the age of the user. For instance, module 1 for 0-6 years, module 2 for the age of 7-12 years, and module 3 for the age of 13-18 years.